Physicochemical properties of fermented and non-fermented rice bran flour and its utilization in bread making - B.O.T, Ifesan; Ifesan, B. T; A.K, Orogbangba (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2015)
Rice bran was subjected to natural fermentation for 4 days and investigated for its physicochemical, antioxidant, phytochemical, functional properties and mineral content. In addition, the fermented and non-fermented rice bran flours were supplemented with wheat flour in several ratios for baking bread. The proximate composition results obtained showed that fermented rice bran flour possessed protein content of 5.68%, fibre (37.8%), fat (2.97%) and carbohydrate (31.06). It was observed that the total phenol content for non-fermented rice bran flour (362.69 GAE Âµg/ml) was higher than fermented bran flour (359.15 GAE Âµg/ml). However, the ability of the samples to scavenge 1,1-di phenyl-2-picrylhydrazyl (DPPH) radical was higher in fermented flour (57.0mg/ml) than in non-fermented sample (55.0 mg/ml). The result of the qualitative analysis of the phytochemical screening revealed that only saponin was present in the rice bran flours. The mineral composition of the non-fermented and fermented rice bran flours revealed that the flours possessed magnesium (0.19%-0.18%), sodium (0.06%-0.17%), calcium (0.08%-0.13%) and potassium (0.03%-0.02%). The physical properties of bread sample at 20% rice bran flour supplementation showed that there was no significant difference between loaf volume of the wheat flour bread and non-fermented rice bran bread (360cm3) while there was significant difference in the loaf volume of fermented rice bran bread (281cm3). It was observed that the fermented rice bran bread had the highest fibre content (1.83%), followed by non-fermented rice bran bread (1.37%) and wheat flour bread (0.95%). The sensory analysis revealed that both the fermented and non-fermented rice bran breadswere scored above average in all sensory parameters although wheat flour bread was preferred.Â